Pemanfaatan Media Sosial Instagram, Facebook dan Whatsapp dalam Meningkatkan Jumlah Customer pada Sindu Arta Tranportasi & Tour Bali - Gama, Agus Wahyudi Salasa; Artawan, I Putu Gede Bayu; Wahyuni, Ika (Universitas Triatma Mulya, 2025)
Sindu Arta Transportasi & Tour Bali is a company operating in the service sector, offering car rentals and tour packages in Bali. The company is located at Jalan Nangka Selatan, Gang Paksimas VI No. 8A, Denpasar. This community service activity was conducted at the aforementioned company with the objective of increasing customer numbers by leveraging social media as a promotional and communication tool. The activity spanned one month, from July 18 to August 19, 2024. The program achieved a 100% success rate in its implementation. The activities included designing pamphlets or posters showcasing the tour and transportation packages offered by Sindu Arta Transportasi & Tour Bali, aiming to boost customer interest in booking these services. Furthermore, social media platforms were utilized as marketing channels for the company's services. Promotional efforts were carried out through Facebook by advertising in the marketplace, Instagram by creating Instagram Stories featuring the previously designed pamphlets, and WhatsApp as a communication medium for detailed service offerings. In conclusion, the utilization of social media in this community service activity effectively enhanced customer interest in the services provided by the company.